Whole Genome Sequencing and Metabolomic Study of Cave Streptomyces Isolates ICC1 and ICC4 - Gosse, Jessica Thandara; Ghosh, Soumya; Sproule, Amanda; Overy, David; Cheeptham, Naowarat; Boddy, Christopher N. (Frontiers in Microbiology, 2019)
The terrestrial subsurface microbiome has gained considerable amount of interests in the recent years because of its rich potential resource for biomining novel genes possessing antimicrobial activities. In our previous study, we identified two Streptomyces isolates, designated as ICC1 and ICC4, from the Iron Curtain Cave, Chilliwack, Canada that exhibited antagonistic activities against the multidrug resistant (MDR) strains of Escherichia coli. In this study, whole genome sequences of the two isolates were sequenced by Illumina MiSeq and their genomes assembled and annotated. The genes associated with secondary metabolite production was identified and annotated using the bioinformatics platforms antiSMASH and BAGEL. ICC1 and ICC4 where then cultivated and the metabolome characterized by LC-ESI-HRMS. GNPS was used to identify metabolites from the extracts. ICC1 and ICC4 show a high level of identity with the terrestrial bacteria Streptomyces lavendulae, however they possess a greater secondary metabolite potential. This enhanced secondary metabolite potential may contribute to their enhanced fitness in the Iron Curtain Cave.